Analisis Framing Pemberitaan Upacara Sudhi Wadhani Pada Media Online di Bali - Wiwik Eka Putri, Niluh; Titah Pratyaksa, I Gede (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam Jember, 2025)
The Sudhi Wadani ceremony is an important process in Hinduism in Bali, serving as the official confirmation for non-Hindu individuals who decide to embrace Hinduism according to both traditional customs and national law. This study aims to analyze how online local media, namely Radar Buleleng, Koran Buleleng, NusaBali, Bali Express, and Tribun Bali, frame the coverage of the Sudhi Wadani ceremony through the framing analysis model of Pan and Kosicki. The research method employed is descriptive qualitative, with data collection through online news documentation and framing unit analysis, including syntactic, script, thematic, and rhetorical structures. The findings reveal that local media portray Sudhi Wadani as a sacred process that must be performed with sincere intention, emphasizing aspects of administrative, spiritual, and social validity through quotes from religious figures and involvement from organizations like PHDI. Local media play an active role in shaping public understanding of the importance of the sanctity, legality, and procedures of Sudhi Wadani, thus reinforcing the ritual's position within the religious and legal domains in Bali.